Millet consumption in type 2 diabetics in urban slums of India: a pilot study - Sohil, Pooja; Mahajan, Sudhanshu; Deshmukh, Rupeshkumar; Gothankar, Jayashree; Adhya, Saibal (Intelektual Pustaka Media Utama, 2025)
Diabetes is a leading cause of death and disability worldwide, affecting people regardless of their country, age group, or sex. Considering the growing prevalence of diabetes among low socioeconomic groups in developing countries like India, the present study aims to determine the prevalence of millet consumption in urban slums in Pune, India. A pilot cross-sectional study was conducted at a private medical college’s field practice area in Pune from January to March 2024. The study focused on individuals with type 2 diabetes mellitus. A pre-designed, pretested semi-structured paperless questionnaire in the Kobo tool app was used to collect information on socio-demographic information, consumption of millet, and diabetes-related information. A total of 30 type 2 diabetics were interviewed as a pilot study. Of these, 53.57% were females, and 46.43% were males. The prevalence of millet consumption was 93% in type 2 diabetics. Sorghum was the most consumed millet amongst all other millet. Age >50 years, education >10th pass, and non-alcoholics were significantly associated with satisfactory consumption of millet. Diversifying diets with nutritious foods like millet can help reduce health-related burdens, including type 2 diabetes. This is important for policy-making and prioritizing diabetes self-care interventions.